Atrioventricular plane displacement in female endurance athletes - Wisloff, U.; Helgerud, J.; Stoylen, A.; Ellingsen, O. (Medicine & Science in Sports & Exercise, 2001)
INTRODUCTION: A novel hypothesis for increased ventricular pumping describes the heart as a displacement pump, in which atrioventricular plane displacement (AVPD) is an important mechanism. The hypothesis predicts that AVPD increases at high heart rates. The aim of the present study was to determine whether AVPD increases during exercise at high heart rates. A secondary aim was to study the left ventricular function and dimensions in endurance-trained young female athletes.